Transforming teacher education through innovation - Hatlevik, Ida Katrine Riksaasen; Jakhelln, Rachel Elise; Jorde, Doris (Routledge, 2024)
Teacher Education (TE) in Norway has developed with a strong emphasis on the research-based and practice-oriented professionalization of TE programs led by universities and university colleges. In the past decade, national reforms have emphasized the development of research competence for student teachers, enabling them to continually develop their own and the school’s collective practices. Center for Professional Learning in Teacher Education, called ProTed, the first National Centre of Excellence in Higher Education in Norway, was established in 2012 as a consortium between the University of Oslo and UiT The Arctic University of Norway. ProTed worked as a catalyst for research and development through systematic interventions, evaluation, and dissemination within integrated five-year TE programs. This chapter gives an introduction to this anthology, which presents a selection of ProTed’s innovations. The chapter outlines five thematic sections to help the reader navigate through different types of innovations: 1) development of integrated TE, 2) research literacy in TE, 3) bridging the gap between the university campus and schools (theory and practice), 4) development of professional identity, and 5) video as a means of connecting coursework to teaching practice. Transforming teacher education through innovation